Assessment of Cotinine Reveals a Dose-Dependent Effect of Smoking Exposure on Long-term Outcomes After Renal Transplantation. Issue 9 (September 2015) - Hellemons, Merel E.; Sanders, Jan-Stephan F.; Seelen, Marc A. J.; Gans, Rijk O. B.; Muller Kobold, Anneke C.; van Son, Willem J.; Postmus, Douwe; Navis, Gerjan J.; Bakker, Stephan J. L.
Abstract : Background: Smoking is a risk factor for poor late outcomes in renal transplant recipients (RTR). Smoking exposure can be assessed by self-report and cotinine measurements. We investigated 1 whether use of cotinine as a biomarker for smoking exposure can serve as an alternative for self-report and 2 to compare associations of smoking exposure by self-report and cotinine with outcomes in RTR and assess dose dependency. Methods: Renal transplant recipients were classified as never, former, light (⩽10 cigarettes/day), and heavy smokers (>10 cigarettes/day) according to self-report and analogous categories for urine and plasma cotinine. First, we assessed agreement of self-reported smoking exposure with smoking exposure according urine and plasma cotinine. Second, we compared the associations with graft failure and mortality. Results: Of 603 RTR (age 51.5 ± 12.1 years, 55% men), 36.0% RTR were never, 42.3% former, 10.6% light, and 11.1% heavy smokers according to self-report. The majority (98.6%) of never smokers had nondetectable cotinine. However, 14 and 13 RTR reporting no active smoking had respective urine or plasma cotinine consistent with active smoking. Cotinine-based measurements were dose-dependently associated with mortality and graft failure. Conclusions: Plasma and urine cotinine can serve as an alternative to self-report and were dose-dependently associated with poor late outcomes in RTR. Abstract : Plasma and urine measurements of cotinine are probably better than self-reported smoking histories and are associated with dose dependent mortality rates. Fourteen (of the total 603) reporting no active smoking had detectable cotinine consistent with active smoking. Supplemental digital content is available in the text.